The Purchase Decision of Halal Labeled Products Based on Brand Awareness and Brand Image for Bugis-Makassar Consumers - Karim, Kasnaeny; Tajibu, Muhammad Jibril (Faculty of Economics and Business, Hasanuddin University, 2022)
The study aimed to investigate how brand awareness and brand image influence the purchasing decisions of Bugis-Makassar consumers in Makassar City when buying halal products, given the competitive market and the increasing availability of foreign products. The study utilized a questionnaire distributed to 100 respondents using purposive sampling. The data collected was analyzed using multiple linear regression. The study found that both brand awareness and brand image had a positive and significant impact on the purchasing decisions of Bugis-Makassar consumers when buying halal products. Furthermore, brand awareness and brand image had a significant impact on the purchasing decisions of halal products when analyzed simultaneously. The R value of 51.9% indicates that brand awareness and brand image variables have a strong influence on the purchasing decisions of halal products. The findings of this study have significant implications for businesses operating in the halal product market. Companies should prioritize building brand awareness and creating a positive brand image to attract and retain customers in the competitive market. Furthermore, companies should understand the unique needs and preferences of the Bugis-Makassar community to tailor their marketing strategies accordingly.